Adsorption of N,N-dimethylamine from aqueous solutions by a metal organic framework, MOF–235 - Beltrán-Suito, R.; Pinedo-Flores, A.; Bravo, F.; Ramos-Muñoz, J.; Sun-Kou, M.R. (Taylor and Francis Inc., 2019)
Water-resistant MOF-235 was used to adsorb N,N-dimethylamine (DMA) from aqueous solutions. It was synthesized from terephthalic acid and FeCl3.6H2O under air-free conditions and characterized by its crystalline structure, functional groups and temperature resistance. The kinetic data results were best adjusted to the pseudo-second order model (R2>0.963). The best-fit isotherm, Langmuir model, suggested the adsorption of DMA is localized on homogenously distributed active sites on the surface. This fit was confirmed by the value of β = 1 on the Redlich-Peterson model. Our study suggests that the manipulation of novel materials such as MOF-235 promises new avenues for water treatment solutions.Schematic structure of MOF-235 and its application as adsorbent.
Keywords: Dimethylamine; Adsorption; Metal-organic framework; Aqueous solution; Langmuir adsorption model; Terephthalic acid; Chemical engineering; Chemistry; Inorganic chemistry; Materials science; Physical chemistry; Organic chemistry; Polyester; https://purl.org/pe-repo/ocde/ford#1.04.03